WORKING CAPITAL MANAGEMENT STRATEGY OF HOTELS IN INDONESIA - Anggraini Lestari - 29116102, Rini
Indonesian tourism has shown positive growth and prepared as the economic leading sector by 2020. During 2012-2016 the foreign visitors increased by 70.3% and contributed to the increase of foreign exchange earnings by 58.8%. As the growth in tourism activities, the hotel business grows rapidly as well with the increasing in room supply by 10.6%. In spite of those positive trends, this industry characteristic is considerably very sensitive to external environment and seasonal demand. This condition lead to the declining of profitability by 22.32% and the corporate performance growth was static with 5 years CAGR of 0.43%. This research aims to define the working capital management strategy of Hotels in Indonesia to optimize the corporate performance. The Corporate Performance (Q) was calculated by the ratio of total market value of equity and the book value of total debt divided by the book value of total assets (Caballero, Teruel and Solano, 2014). Fuzzy Set Qualitative Comparative Analysis (fsQCA) method is used to construct the strategy. The data consist of quarterly financial data of 11 companies under subsector hotel, restaurant, and tourism listed in Indonesia Stock Exchange during 2012-2016. The study proposes five possible strategies for working capital management in order to optimize the corporate performance which divided into three groups based on the profitability requirement. There are proposed strategies for the company which has good profitability, poor profitability, and contradictive profitability.